Neutrophil lymphocyte ratio as predictor of mortality in pediatric patients with bacterial meningitis: A retrospective cohort study - Widjaja, Hardiman; Rusmawatiningtyas, Desy; Makrufardi, Firdian; Arguni, Eggi (Elsevier Ltd, 2022)
Background: Bacterial meningitis causes high mortality rates among children. Even with early diagnosis and prompt treatment, around 15 of patients die especially in the first and second days after diagnosis. The neutrophil lymphocyte ratio has been reported to be a predicting factor of severity and outcome for patients with pneumonia and sepsis. However, only a few studies are available to rate the neutrophil lymphocyte ratio as a predictor of mortality in bacterial meningitis. This study aimed to know the role of the neutrophil lymphocyte ratio as a predictor of mortality in patients with bacterial meningitis. Methods: This retrospective study was conducted at Dr. Sardjito General Hospital, Yogyakarta, Indonesia between January 2016 to December 2020. Multivariate analysis was used to assess the correlation between predicting factors and outcomes using logistic regression analysis. Results: A total of 94 samples were included and analyzed in this study with bacterial meningitis. Neutrophil lymphocyte ratio >5.225 was a significant predictor of mortality in patients with bacterial meningitis with p = 0.004 and risk ratio 10.78. Other factors that were significant predictors of mortality included the pediatric coma scale ≤8 and positive cerebrospinal fluid culture. Conclusion: Neutrophil lymphocyte ratio is a statistically significant predictor of mortality in patients with bacterial meningitis, and can be used as a parameter to predict outcomes in patients with bacterial meningitis. © 2021